Low optical loss planar waveguides prepared in an organic-inorganic hybrid system - Ribeiro, SJL; Messaddeq, Younes [UNESP]; Goncalves, R. R.; Ferrari, M.; Montagna, M.; Aegerter, M. A. (American Institute of Physics (AIP), 2000)
HfO2-(3-glycidoxipropil)trimethoxisilane (GPTS) planar waveguides were prepared by a sol-gel route. A stable sol of Hafnia nanocrystals was prepared and characterized by photon correlation spectroscopy and high resolution transmission electron microscopy. The suspension was incorporated in GPTS host and the resulting sol was deposited on borosilicate substrates by the spin coating technique. Optical properties such as refractive index, thickness, number of propagating modes, and attenuation coefficient were measured at 632.8, 543.5, and 1550 nm by the prism coupling technique as a function of the HfO2 content. (C) 2000 American Institute of Physics. [S0003-6951(00)03348-9].